Anti-Inflammatory and Anti-Adipocyte Dysfunction Effects of Ficus lindsayana Latex and Root Extracts - Jirarat Karinchai; Pensiri Buacheen; Daraphan Rodthayoy; Tanpitcha Yodweerapong; Arisa Imsumran; Ariyaphong Wongnoppavich; Bhanumas Chantarasuwan; Uthaiwan Suttisansanee; Piya Temviriyanukul; Pornsiri Pitchakarn (MDPI AG, 2024)
Low-grade chronic inflammation and adipocyte dysfunction are prominent risk factors of insulin resistance and type 2 diabetes mellitus (T2DM) in obesity. Thus, prevention of inflammation and adipocyte dysfunction could be one possible approach to mitigate T2DM development. Several Ficus species have been used in traditional medicine for ameliorating inflammation and T2DM. Our previous studies reported biological effects of Ficus lindsayana including antioxidant, anti-cancer, and anti-α-glucosidase activities. Further, this study therefore investigated whether F. lindsayana latex (FLLE) and root (FLRE) extracts inhibit inflammation-stimulated insulin resistance in adipocytes and inflammation in macrophages. FLLE and FLRE (200 µg/mL) had no significant cytotoxicity for macrophages, adipocytes, and blood cells (PBMCs and RBCs). FLRE had a total flavonoid content about three times higher than FLLE, while both had similar levels of total phenolic content. FLRE showed higher abilities than FLLE in suppressing inflammation in both macrophages and adipocytes and reversing the inflammation-induced insulin resistance in adipocytes. In TNF-α-induced adipocytes, FLRE significantly improved insulin-induced glucose uptake and insulin-suppressed lipolysis, while FLLE only significantly improved glucose uptake. Moreover, FLRE and FLLE remarkably reduced chemoattractant (MCP-1) but improved adipogenic (PPARγ and CEBPα) gene expression, leading to the promotion of adipogenesis and the suppression of insulin resistance. In LPS-induced macrophages, FLRE, but not FLLE, significantly inhibited LPS-induced NO production. Moreover, FLRE significantly reduced LPS-stimulated iNOS, COX-2, IL-1β, IL-6, and TNF-α gene expression. These results may provide the potential data for the development of this plant, especially the root part, as an alternative medicine, functional ingredient, or food supplement for the prevention of inflammation and obesity-associated insulin resistance, as well as T2DM.